Phenotypic and molecular characterization of fusarium spp. coming from sesame production zone in Venezuela - Laurentin, Hernán; Alvarado, Gilberto; Querales, Pastora; Ulacio, Dilcia; Gómez, Ana; Méndez, Naileth (Biotecnología en el Sector Agropecuario y Agroindustrial, 2019)
Sesame is an important crop in tropical areas, which is seriously affected by soil-borne fungi such as Macrophomina phaseolina and Fusarium sp. In order to identify and characterize Fusarium spp. causing disease in sesame plants in the field, ten isolates were obtained. Eleven distinctive taxonomic traits were determined, and additionally growth rate was measured in Petri dishes. Random Amplified Polymorphic DNA (RAPD) by means of five primers was also performed. Three Fusarium species were reported: Fusarium oxysporum (2 isolates), Fusarium solani (7 isolates) and Fusarium semitectum (1 isolate). Previous reports indicate that sesame is affected just by F. oxysporum f. sp. sesami, only one previous report indicate that also F. solani causes fusarium wilt in this crop. In vitro growth rates were within a range of 0,21-0,29 mm h-1, with no trend according to the species. Growth of one of the isolates of F. oxysporum was statistically (P<0.05) faster than the others. Fifty RAPD bands (92% polymorphic) were not able to differentiate the three Fusarium species. Similarity Jaccard coefficient ranged between 0,15 and 0,47 with an average of 0,32.